Hardware implementation of a peak-to-average power ratio reduction - Varahram, Pooria; Mohd Ali, Borhanuddin; Mohammady, Somayeh; Sulaiman, Nasri (2014)
Orthogonal frequency division multiplexing (OFDM) has a main drawback namely high peak-to-average power ration (PAPR) which as the result power effiency of a system degrades. Several methods have been devised to overcome this drawback, one example of which is partial transmit sequence (PTS). In this paper, a field programmable gate array (FPGA) implementation of a PTS scheme in order to reduce PAPR in OFDM systems is carried out. The integration of PTS with digital pre-distortion technique improves the system effiency, suppressed out-o-band distortion and hence, prolong baterry life. The simulations have been carried out with QPSK modulation and inverse fast Fourier transform (IFFT) with QPSK modulation and inverse fast Fourier transform (IFFT) with 1024 subcarriers. The hardware results show in average 21% reduction in hardware resource and almost 18% conservation in total power consumption by applying the PTS scheme.